Features of enzymatic activity of a digestive path of young of salmon fishes - T. S. Ershova; I. V. Volkova (Юг России: экология, развитие)
In the work activity of some digestive enzymes participating in hydrolysis нутриентов of the albuminous and carbohydrate nature at молоди Black Sea кумжи Salmo trutta labrax Pallas and стальноголового of salmon Salmo gairdneri Rich has been investigated.